Contracting with private providers for primary care services: Evidence from urban China - Yan Wang; Karen Eggleston; Zhenjie Yu; Qiong Zhang (Health Economics Review, 2013)
Controversy surrounds the role of the private sector in health service delivery, including primary care and population health services. China's recent health reforms call for non-discrimination against private providers and emphasize strengthening primary care, but formal contracting-out initiatives remain few, and the associated empirical evidence is very limited. This paper presents a case study of contracting with private providers for urban primary and preventive health services in Shandong Province, China. The case study draws on three primary sources of data: administrative records; a household survey of over 1600 community residents in Weifang and City Y; and a provider survey of over 1000 staff at community health stations (CHS) in both Weifang and City Y. We supplement the quantitative data with one-on-one, in-depth interviews with key informants, including local officials in charge of public health and government finance. We find significant differences in patient mix: Residents in the communities served by private community health stations are of lower socioeconomic status (more likely to be uninsured and to report poor health), compared to residents in communities served by a government-owned CHS. Analysis of a household survey of 1013 residents shows that they are more willing to do a routine health exam at their neighborhood CHS if they are of low socioeconomic status (as measured either by education or income). Government and private community health stations in Weifang did not statistically differ in their performance on contracted dimensions, after controlling for size and other CHS characteristics. In contrast, the comparison City Y had lower performance and a large gap between public and private providers. We discuss why these patterns arose and what policymakers and residents considered to be the main issues and concerns regarding primary care services.
Keywords: 330; private providers; contracting; ownership; primary care; prevention; China